Evidence for Recent Large Magnitude Explosive Eruptions at Damavand Volcano, Iran with Implications for Volcanic Hazards - M. Mortazavi (Journal of Sciences, Islamic Republic of Iran)
Damavand is a large dormant stratovolcano in the Alborz Mountains of northern Iran located in one of the most populous provinces, which could be adversely affected by tephra fall from Damavand. The youngest known eruption is a lava flow on the western flanks with an age of 7.3 ka. The volcanic products are predominantly porphyritic trachyandesite. Three major young pumice deposits, named here as Mallar, Karam Poshteh and Reyneh pumices, are identified, with provisional ages in the interval >7.3 ka and < 25 ka. The deposits cover much of the southern and western flanks of the volcano. The Mallar and Reyneh deposits consist of extensive basal pumice fall deposits with dispersal axes to the east, overlying pumiceous pyroclastic flow deposits extending up to 20 km from the summit and late-stage lahar deposits. The middle unit (Karam Poshteh) consists of a coarse-grained pumice fall deposit with proximal welded facies dispersed to the west, but lacks pyroclastic flow deposits. Based on reconnaissance field data they were formed by explosive eruptions of VEI4. Some of the villages on the flanks of the volcano are built on pyroclastic flow and lahar fans, and thus would be at high risk in the event of future explosive eruptions. We present an analysis of wind data and the applications of a computer tephra dispersal model to assess tephra fall hazards. Explosive eruptions of Damavand in the future would adversely affect large cities in the neighbouring provinces to the east, reflecting the dominant regional stratospheric wind directions.